Cognitive diversity of geographical sources contents about middle Maghreb - berzag, nadir (The Algerian Historical Journal, 2026)
The Geographers recorded many historical facts about economic, social and others.They also mentioned climate conditions and nature potentialities ,these were the core concern of geographic books. The geographer's methodology of distinction was present to make difference between rural and urban side since differences existed between them. So, what was the value of geographic resources in displaying the towns' civilisational aspect in economic, social and others ? Our aim in this article is to know the aspects of some Algerian towns as examples during the 3rd hijiri century (9th century BC) and the 10th hijiri century (16th century BC) .We came to the conclusion that geographer's methodology differed in general and detailed description. The economic situation was dominant comparing to other fields, however, these historical information let searchers make an image of some events and historical evolution.